EFEKTIVITAS BEHAVIOUR THERAPY TERHADAP RISIKO PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PROF. Dr. MUHAMMAD ILDREM PROVSU MEDAN - Pardede, Jek Amidos; Siregar, Laura Mariati; Hulu, Efendi Putra (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The risk of violent behavior is a symptom of schizophrenic patients that can be controlled through Behavior Therapy. Behavior Therapy is one approach to understanding the behavior of individuals who perceive individuals in terms of physical phenomena, and tend to ignore mental aspects. The purpose of this study was to determine the effect of Behavior Therapy on changes in symptoms of the risk of violent behavior in schizophrenic patients. This study used the quasi experimental pre-post test method. The population in this study amounted to 155 people with a total sample of 13 people. The sampling technique is purposive sampling. The research instruments used were questionnaires, SOP standart operation prosedurt and observation sheets. The results of this study were analyzed by univariate analysis and bivariate analysis with Paired T-Test. The results showed that there was an effect of Behavior Therapy on Changing Symptoms of Violent Behavior Risk before and after doing Behavior Therapy Researchers concluded that Behavior Therapy had a significant effect on changes in symptoms of the risk of violent behavior in Prof.Dr.Muhammad Ildrem Provsu Medan Hospital marked with Pvalue = 0,000 <p = 0.05. It is recommended for the hospital to provide a special place / place to conduct Behavior Therapy so that the respondent stays concentrated in following Behavior Therapy